Diagnosis value of some acute-phase proteins in purulent-inflammatory diseases of uterine appendages - S. V. Shramko; S. V. Arkhipova; L. G. Bazhenova; R. M. Zorina (Бюллетень сибирской медицины, 2006)
We investigated concentrations of acute-phase proteins a-2-macroglobulin (MG) and lactoferrin (LF) in blood serum of 78 women with various types of uterine appendages inflammatory processes. Coefficient MG/LF was used as an additional diagnostic criterum of purulent-necrotic destruction of organs and tissues and allowed us to choose proper treatment options. MG values were assessed by method of rocket immune electroforesis using monospecific antiserum to the given protein, LF level was assessed by enzyme linked immunoassay based method (ELISA). Standard was performed when coefficient MG/LF was greater than 1, and if value of coefficient MG/LF was less than 1, we performed surgical treatment. Using coefficient MG/LF as a diagnostic criterion of existence of organic destruction in uterine appendages allowed us to optimize the selection of treatment program.